Inflation and unemployment revisited: Grease vs. sand - Erica L. Groshen; Mark E. Schweitzer (Goethe University Frankfurt, Center for Financial Studies (CFS), 1998)
As inflation rates in the United States decline, analysts are asking if there are economic reasons to hold the rates at levels above zero. Previous studies of whether inflation greases the wheels of the labor market ignore inflation's potential for disrupting wage patterns in the same market. This paper outlines an institutionally-based model of wage-setting that allows the benefits of inflation (downward wage flexibility) to be separated from disruptive uncertainty about inflation rate (undue variation in relative prices). Our estimates, using a unique 40-year panel of wage changes made by large mid-western employers, suggest that low rates of inflation do help the economy to adjust to changes in labor supply and demand. However, when inflation's disruptive effects are balanced against this benefit the labor market justification for pursuing a positive long-term inflation goal effectively disappears.
urn:nbn:de:hebis:30-9568
Keywords: E31; E52; J30; 330; Inflation; Nominal Wage Rigidity; Wage Setting